(untitled) (Advances in Civil and Architectural Engineering, 2021)
The objective of this article is to show the design process of a liquid-storage tank shell according to Eurocode and compare the results obtained using the norms with those from a finite element method (FEM) analysis. The calculations were performed for an aboveground vertical steel water-storage tank with a variable thickness wall and stiffening ring on top. First, the types of liquid storage tanks are briefly explained. Second, the given tank is described. Third, an analysis of the tank wall according to the Eurocode was carried out. The FEM analysis was performed using the Scia Engineer ver. 17 software. Finally, all the results are presented in tables and compared.